2016
DOI: 10.1212/wnl.0000000000003326
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous cortical atrophy patterns in MCI not captured by conventional diagnostic criteria

Abstract: Objective: We investigated differences in regional cortical thickness between previously identified empirically derived mild cognitive impairment (MCI) subtypes (amnestic MCI, dysnomic MCI, dysexecutive/mixed MCI, and cluster-derived normal) in order to determine whether these cognitive subtypes would show different patterns of cortical atrophy.Methods: Participants were 485 individuals diagnosed with MCI and 178 cognitively normal individuals from the Alzheimer's Disease Neuroimaging Initiative. Cortical thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 26 publications
9
70
0
Order By: Relevance
“…These results add to the accumulating body of evidence that the CDN group – which accounts for a significant proportion of the ADNI MCI cohort – represents false positive diagnostic errors (Bangen et al, 2016; Bondi et al, 2014; Edmonds et al, 2014, 2015, 2016; Eppig et al, 2017; Thomas et al, 2017). Previous studies have suggested that MCI patients have intact awareness of their cognitive abilities (for review, see Piras et al, 2016), which appears contrary to our results.…”
Section: Discussionsupporting
confidence: 59%
“…These results add to the accumulating body of evidence that the CDN group – which accounts for a significant proportion of the ADNI MCI cohort – represents false positive diagnostic errors (Bangen et al, 2016; Bondi et al, 2014; Edmonds et al, 2014, 2015, 2016; Eppig et al, 2017; Thomas et al, 2017). Previous studies have suggested that MCI patients have intact awareness of their cognitive abilities (for review, see Piras et al, 2016), which appears contrary to our results.…”
Section: Discussionsupporting
confidence: 59%
“…When comparing Jak/Bondi and conventional criteria, conventional MCI diagnostic methods resulted in about 33% false‐positive and 7% false‐negative error rates [28,29,50]. In support of the Jak/Bondi criteria, the “false‐positive” subgroup performed within normal limits across the cognitive battery and showed cerebrospinal fluid biomarker levels, cortical thickness maps, and rates of progression to dementia that were comparable to a robust NC group [28,29,51]. The “false‐negative” group showed cerebrospinal fluid biomarker levels that were comparable to the MCI group and progressed to dementia at double the rate of the overall NC sample [50].…”
Section: Discussionmentioning
confidence: 91%
“…Impairment was defined as >1.5 standard deviations below the mean of the HC. Patients were determined to be impaired in the language domain if two or more of the three cognitive tests fell within the impairment range . Patients missing only one of the three tests were included and classified as impaired if both tests fell within the impairment range.…”
Section: Methodsmentioning
confidence: 99%